Optyczna koherentna tomografia w diagnostyce schorzeń siatkówki u dzieci i młodzieży - Mrugacz, Małgorzata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
This report describes the new optical technique of optical coherence tomography (OCT) for imaging eye fundus. OCT is noninvasive, capable of high-resolution of 10 to 17 µm imaging of biological tissue. It has been used, to investigate several ocular diseases in children and adolescents. These include macular disease, glaucoma, optic nerve disorders, and myopia.